Enhanced catalytic conversion of disaccharides to propylene glycol using metal-supported graphitic carbon nitride - Kirali, Arun Arunima Balachandran; Narayanan, Hariprasad; Viswanathan, Balasubramanian; Yadav, Parmeshwar; Marimuthu, Banu (Energy and Fuels, 2024)
Propylene glycol (or) 1,2-propanediol (1,2-PD) is an important polyol widely used for pharmaceuticals, polyester resins, paints, cosmetics, antifreeze, etc. Sucrose has emerged as a promising feedstock to produce 1,2-PD, as indicated by recent research findings. Graphitic carbon nitride (g-C3N4/gCN) was synthesized by using different crucibles. Ni-Mo was loaded on different g-C3N4 supports via the wetness impregnation method for sucrose hydrogenolysis. Effects of different g-C3N4 supports were studied. Catalysts with varying Ni (x = 0-8 wt %) and Mo (y = 0-15 wt %) contents were characterized using XRD, BET, XPS, FE-SEM, Py-FTIR, HR-TEM, TPD (CO2)and Raman spectroscopy. An attempt was made on sucrose conversion into 1,2-PD using a Ni-Mo/g-C3N4 catalyst. The catalyst containing 8% Ni and 10% Mo on Gr-gCN exhibited the best performance, achieving complete sucrose conversion with a 76% yield of 1,2-PD under mild reaction conditions. The presence of highly dispersed nanoparticles and the nature of graphitic carbon nitride help improve the reactions' yield by allowing reactions at lower temperatures, reducing the occurrence of side reactions, and increasing recycling rates. A straightforward approach to material preparation, coupled with the exceptional dispersion of metal nanoparticles, paves the way for a novel platform for biomass conversion.

One-pot catalytic conversion of sucrose to 1,2-propanediol over titania supported Ni-Ce metal catalyst under milder reaction conditions - Sreekantan, Sreejith; Sreedharan, Sarath; Kirali, Arun Arunima Balachandran; Yadav, Parmeshwar; Marimuthu, Banu (Biomass Conversion and Biorefinery, 2024)
The increased energy demand and decreasing fossil resources have driven the research community to look into a sustainable, green process to meet the energy demands. India being one of the top producers of sugarcane derived sucrose, and conversion of surplus sucrose to value chemicals is always an advantage. 5%Ni-15%Ce/TiO2 catalyst is found to produce high yield of 1,2-PDO (similar to 74%) under very mild reaction condition of 180 degrees C, 30 bar H-2 for 3-h reaction time. The characterization of the catalyst by using various physicochemical methods indicates the synergy between Ni-Ce bimetal which enhances the selective production of glycol. The low temperature and pressure requirement and the advantage of being the one-pot process will always attract the future scope of commercialization.
Keywords: Glycol; Low pressure; Low temperature; Ni-Ce catalyst; Sucrose; titania